THE SHEIKH ABD SHAMAD AL-PALIMBANI THOUGHTS OF ETHICS FOR STUDENT AND TEACHER AND IT’S RELEVANCE TO THE 21st CENTURY EDUCATION: A STUDY OF SAIR AS-SALIKIN - Agustina, Riza; Munip, Abdul; Sa'adah, Susan (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
The study of Islamic education theory has so far prioritized the thinking of educational scholars from the Arab world. However, the study of Islamic educational thought of Nusantara scholars still needs to be encouraged. One of the Nusantara scholars who was very instrumental in the Indonesian Islamic intellectualism tradition was Sheikh Abd Shamad al-Palimbani (1704-1789). This article aims to explain al-Palimbani's educational thoughts, especially on the ethical aspects of a student and teacher, as well as its relevance to the educational practices today. The main data source of this article is al-Palimbani's work entitled Sair as-Salikin. The content analysis is used to analyze and explain the work. This article finds that in al-Palimbani's view, a student must have ethics both relating to himself and relating to his teacher. Some of the ethics are a student must be clean of his heart from despicable nature, focus on study, redempted, respect knowledge, intention because of God, respect the teacher, and not feel smarter than his teacher. Meanwhile, a teacher should be patient, affectionate with students, humble, accept the truth of other opinions, not expect rewards, resuscitate students and others. It some points of al-Palimbani's educational thought that are still very relevant to the characteristics of 21st century education. Among them are the importance of mutual respect between students and teachers, honesty in communicating, openness in accepting the truth, and lifelong learning. At least, al-Palimbani's educational thougths are relevant to the characteristics of 21st century education, in expecting rewards from teaching activities and excessive restrictions on students when in the presence of teachers